Selective inhibition of metabotropic glutamate type 1 alpha receptor (mGluR1α) reduces cell proliferation and migration following status epilepticus in early development. Issue 54 (November 2016) - Friedman, L.K.; Sharma, A.; Corcia, M.; Webster, T.; Qazi, L.; Simsovits, D.; Khalil, Y.; Hu, S.; Kantrowitz, M.; Hong, H.
Abstract: The present study examined whether a single or multiple episode(s) of status epilepticus induced with kainic acid (KA) during the first 3 weeks of postnatal (P) development would aberrantly stimulate proliferation zones that alters migration to potentially injured areas and whether they would be blocked by selective Group I mGluR antagonists. mGluR1α (LY367385) and mGluR5 (MPEP) antagonists were administered 2 h following KA-induced status epilepticus and animals were examined after 7 days. Proliferating cells of the subventricular zone (SVZ), third ventricle, hippocampus, amygdala cortical complex were analyzed with the proliferative marker, Ki67; and two complementary retrograde dye tracers. Proliferation increased in extrahippocampal limbic structures when KA was administered on P13 or P20 which correlated with number of injured cells at the older age. LY367385 post-treatment caused striking decreases in proliferation in all limbic structures in the presence and absence of injury, whereas a reduction with MPEP was observed only within the amygdala cortical complex (Amg/ERcx) in the presence of multiple seizures (3 × KA). After 3 × KA and LY367385 post-treatments, diminished co-staining of dye tracers with Ki67 was observed within the Amg/ERcx despite high levels of progenitors marked by the retrograde tracers in this region. This indicates that not only was local proliferation within the SVZ and distant structures inhibited, but also that migration itself was reduced indirectly since there were less cells to migrate from the SVZ. Co-labeling with biomarkers provided evidence for neuronal differentiation suggesting potential aberrant integration may occur in distant locations, and that targeting of mGluR1α receptors may be a potential therapeutic strategy for future development.